-6(-4x+7)-5x=3(x-6)-6

Simple and best practice solution for -6(-4x+7)-5x=3(x-6)-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(-4x+7)-5x=3(x-6)-6 equation:



-6(-4x+7)-5x=3(x-6)-6
We move all terms to the left:
-6(-4x+7)-5x-(3(x-6)-6)=0
We add all the numbers together, and all the variables
-5x-6(-4x+7)-(3(x-6)-6)=0
We multiply parentheses
-5x+24x-(3(x-6)-6)-42=0
We calculate terms in parentheses: -(3(x-6)-6), so:
3(x-6)-6
We multiply parentheses
3x-18-6
We add all the numbers together, and all the variables
3x-24
Back to the equation:
-(3x-24)
We add all the numbers together, and all the variables
19x-(3x-24)-42=0
We get rid of parentheses
19x-3x+24-42=0
We add all the numbers together, and all the variables
16x-18=0
We move all terms containing x to the left, all other terms to the right
16x=18
x=18/16
x=1+1/8

See similar equations:

| 25x+16=25x+71 | | 10x+5=4x-8 | | 25x-17=5+25x | | 5.4+0.75x=15.4-0.5x | | 56+51+n=180 | | 5x–10=15 | | 20x+2=-30x+15 | | 5f-6+4f=f+2 | | 45x+165=20 | | (2x+4)+(2x+4)+(3x+7)=8x | | (m)/(7)=3 | | 4(x+6)+4x+16=360 | | 6(-3k-8)+12=-9k | | 10x+5=4x-6 | | 2(x-18)-10=5x+2 | | -5x+7=-x+43 | | 3−5(x+4)=8(2x−3) | | 7(x-15)=-28 | | -7x+40=12 | | 6.9=a-3.4 | | 5t-4=5t+4 | | -6q=-18+2q | | 2z=–58 | | y+6.5=-12 | | 150m-125m+43200=46125-200m | | 10=x/2-5 | | h+1/2=3 | | 3h-h-1=7 | | 1/2(6x+6)=3x+13 | | 125m-100m+38,000=40,600-175m | | 2x+9=8x+6 | | 2x+4+3x=-25+4 |

Equations solver categories